The switch ebook A novel. - O'Leary, Beth (2020)
A grandmother and granddaughter swap lives in The Switch , a charming, romantic novel by Beth O'Leary, who has been hailed as "the new Jojo Moyes" ( Cosmopolitan UK )... When overachiever Leena Cotton is ordered to take a two-month sabbatical after blowing a big presentation at work, she escapes to her grandmother Eileen's house for some long-overdue rest. Eileen is newly single and about to turn eighty. She'd like a second chance at love, but her tiny Yorkshire village doesn't offer many eligible gentlemen. So they decide to try a two-month swap. Eileen will live in London and look for love. She'll take Leena's flat, and learn all about casual dating, swiping right, and city neighbors. Meanwhile Leena will look after everything in rural Yorkshire: Eileen's sweet cottage and garden, her idyllic, quiet village, and her little neighborhood projects. But stepping into one another's shoes proves more difficult than either of them expected. Will swapping lives help Eileen and Leena find themselves...and maybe even find true love? In Beth O'Leary's The Switch , it's never too late to change everything....or to find yourself.